EVALUACION DEL HIPOTETICO SISTEMA DE FALLA TRANSCURRENTE ESTE-OESTE DE COSTA RICA - Fernández Arce, Mario (2011)
The following criteria were analysed in order to evaluate the existence of the hipotetic transcurrentfaults system (FTCR) of Costa Rica in its central part: geologic setting, faulting, earthquakes distribution, focalmechanisms, deep transcurrence, and gravimetric data.The predominant faulting is the one with northwest orientation, secondly the faulting with the northeast orienta-tion. This faulting is more abundant in the Talamanca Ridge rather than in the Central Volcanic Ridge. Faultsoriented east-west, a necesary requirement for the existence of FTCR, are scarce.The distribution of epicenters indicates that in both ridges there are seismic sources. In the Central Volcanic Ridge earthquakes take place in spaces between volcanoes. In the Talamanca Ridge there are at least five very activeseismic zones. Earthquakes with more than 5-degrees in magnitud occur in both ridges. Focal mechanisms aremainly normal. Transcurrent mechanisms suggest an active faulting oriented Northwest.There is no correlation between gravimetric lineament and the FTCR. To conclude, there is no geophysical evidence of the FTCR in the central part of Costa Rica.